Development and validation of an UPLC-ESI-MS/MS method for quantification of duvelisib in plasma: application to pharmacokinetic study in rats. Issue 12 (10th March 2023) - Darwish, Ibrahim A.; Alzoman, Nourah Z.; Almomen, Aliyah; Almehizia, Abdulrahman A.; Attwa, Mohamed W.; Darwish, Hany W.; Sayed, Ahmed Y.
Abstract : Duvelisib (DUV) is a new oral phosphoinositide-3-kinase (PI3K)-δ and PI3K-γ inhibitor. Abstract : Duvelisib (DUV) is a new oral phosphoinositide-3-kinase (PI3K)-δ and PI3K-γ inhibitor. It is used for the treatment of relapsed or refractory chronic lymphocytic leukemia (CLL) and small lymphocytic lymphoma (SLL). This study describes the development and validation of a new highly sensitive and efficient UPLC-ESI-MS/MS method for quantitation of DUV in plasma samples and its application to the pharmacokinetic study of DUV in rats. The method employed a very simple step for plasma sample pretreatment via precipitation of protein using methanol. DUV and ceritinib (CRB) as an internal standard (IS) were separated on a porous Hypersil BDS-C18 column (125 mm × 2 mm, 3 μm) using a mobile phase consisting of ammonium formate (10 mM, pH 4.2):acetonitrile (42 : 58, v/v), pumped isocratically at a flow rate of 0.3 mL min −1 . DUV and CRB were eluted at 0.58 and 1.10 min, respectively. The mass spectrometric analysis was performed using an ESI in positive mode with multiple reaction monitoring (MRM). The technique was validated in accordance with the standards for validating bioanalytical methods established by the International Conference on Harmonization (ICH). The method's linear range was 5–500 ng mL −1, and its correlation coefficient was satisfactory as it is almost unity (0.9999). The limit of quantitation (LOQ) was 5 ng mL −1, while the limit of detection (LOD) was 1.7 ng mL −1 . The recovery of the spiking DUV was between 94.95 and 102.21%, and the relative standard deviation (RSD) was less than 2.70%, confirming the method's accuracy and precision. The specificity/carryover of the method was proved. The robustness and ruggedness of the method was proved as the recovery values were 97.6–101.96% (±01.17–2.20%) and 98.74–102.00 (±1.18–4.02%) for robustness and ruggedness, respectively. The stability of DUV under the different analytical conditions were documented as the recovery values were in the range of 95.89–103.28% and the RSD values did not exceed 7.36%. The method was efficiently used to analyze DUV in human plasma samples that had been spiked with DUV and to conduct pharmacokinetic investigations of DUV in rats after giving them a single oral dosage of 25 mg kg −1 of the drug. The methodology is distinguished by excellent sensitivity, accuracy, and ease of sample pretreatment. Furthermore, it is efficient and has a short run time, which makes it high throughput and accordingly enables faster processing of many samples in clinical laboratories.